The problem of Aphasia in children - H, Venkatagiriappa (Journal of All India Institute of Speech and Hearing, 1970)
While aphasia in adults has attracted much research and clinical studies, corresponding literature in the field of ’aphasia’ in children is wanting. There is a fundamental question as to whether there exists an entity called ’aphasia in children.’ Some deny the existence of aphasia in children on neuroanatomical and neurophysiological considerations (Sugar 1952). However, all the workers in the field are unanimous on one point, i.e., there is a category of children whose inability or inefficiency in acquiring language cannot be ascribed to (a) mental retardation, (b) sensory involvement, (c) motor disability and/or incoordination and (d) emotional disturbances and/or (e) lack of environmental stimulation. A majority of the workers are inclined to call these children aphasics. However, there are at least three differences between adult aphasics and these children